2018
DOI: 10.1038/s41598-018-22594-1
|View full text |Cite
|
Sign up to set email alerts
|

PSMA expression: a potential ally for the pathologist in prostate cancer diagnosis

Abstract: Prostate cancer (PCa) patients are risk-stratified on the basis of clinical stage and PSA level at diagnosis and the Gleason Score (GS) in prostate biopsy. However, these parameters are not completely accurate in discriminating between high- and low-risk disease, creating a need for a reliable marker to determine aggressiveness. Prostate-specific membrane antigen (PSMA) appears to fulfill this need. We analyzed 79 prostate biopsies and 28 prostatectomies to assess whether PSMA expression detected by immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
109
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(120 citation statements)
references
References 31 publications
8
109
0
3
Order By: Relevance
“…The pooled detection rate was 70.2% for the entire cohort, ranging from 44.9% for a PSA level of less than 0.5 ng/mL to 93.9% for a PSA level of at least 2 ng/mL on stratified subgroup analysis. All the studies showed a maximal detection rate at a PSA level of at least 2 ng/mL, with rates of around 90%, as is consistent with the fact that around 5%-10% of PCa do not overexpress PSMA and are thus PSMA-negative (70). The authors concluded that PSMAtargeted radiotracers are likely effective for the detection of BCR at low PSA levels, but there was significant study heterogeneity (I 2 of 95.6% for the entire cohort) due to differences in inclusion criteria, study populations, methodology, radiotracers used, retrospective designs, and reference standards.…”
Section: Imaging In Bcr and Recurrent Disease After Treatmentsupporting
confidence: 80%
“…The pooled detection rate was 70.2% for the entire cohort, ranging from 44.9% for a PSA level of less than 0.5 ng/mL to 93.9% for a PSA level of at least 2 ng/mL on stratified subgroup analysis. All the studies showed a maximal detection rate at a PSA level of at least 2 ng/mL, with rates of around 90%, as is consistent with the fact that around 5%-10% of PCa do not overexpress PSMA and are thus PSMA-negative (70). The authors concluded that PSMAtargeted radiotracers are likely effective for the detection of BCR at low PSA levels, but there was significant study heterogeneity (I 2 of 95.6% for the entire cohort) due to differences in inclusion criteria, study populations, methodology, radiotracers used, retrospective designs, and reference standards.…”
Section: Imaging In Bcr and Recurrent Disease After Treatmentsupporting
confidence: 80%
“…PSMA was reported to promote cancer progression and malignant transformation at least in part via neovascularization [12,13]. Immunohistochemical analysis revealed increased PSMA expression in primary and metastatic lesions of prostate cancer compared with normal prostate, and PSMA expression was reported to correlate with Gleason score and cancer aggressiveness [13,14] [26]. As opposed to these data, in this study, there was no significant association between Gleason score and PSMA expression in CTC ( Table 2), suggesting that PSMA in CTCs is an independent poor prognostic marker.…”
Section: >0999mentioning
confidence: 99%
“…PSMA is expressed in most PCa tissues and its expression often increased in metastatic, poorly differentiated, androgen-independent, and hormone-refractory carcinoma [2][3][4]. In addition, the levels of PSMA expression correlate with the progression, stage, and the risk of disease [5,6]. Therefore, PSMA is considered to be a promising, reliable, and an efficient biomarker for PCa imaging and therapeutic application.…”
Section: Introductionmentioning
confidence: 99%